SELF-REFLECTION TECHNIQUES TO INCREASE SELF-ACCEPTANCE IN MAN TEBING TINGGI STUDENTS - Dihra Ardaly Siregar; Ramadan Lubis (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to reveal the experiences of students in practicing muhasabah (self-reflection) and to examine how these experiences contribute to the formation of self-acceptance. The research employs a qualitative approach with a case study design, which allows for an in-depth exploration of the subjective meanings constructed by participants through their spiritual experiences. The research subjects consisted of two tenth-grade students from MAN Tebing Tinggi, selected through purposive sampling, along with two supporting teachers: a Guidance and Counseling (BK) teacher and an Islamic Religious Education (PAI) teacher. Data were collected through in-depth interviews, non-participatory observation, and reflective documentation. The findings indicate that muhasabah, carried out both through school-based religious activities and personal reflection, has a positive impact on how students perceive themselves. This process helps students to understand and accept their shortcomings, cultivate gratitude, and strengthen their spiritual connection with Allah SWT. Additionally, acceptance of destiny (takdir) plays a significant role in fostering inner peace and sincerity in dealing with life’s realities. These findings emphasize that muhasabah affects not only the spiritual aspect but also contributes meaningfully to the psychological well-being of students. In the context of Islamic education, muhasabah can be integrated as a reflective strategy to develop character and strengthen students’ self-acceptance. This study contributes to the development of Islamic counseling that emphasizes internalized values and the holistic formation of self-awareness.